2013
DOI: 10.1016/j.celrep.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling Triggers Neuron Reprogramming and Regeneration in the Mouse Retina

Abstract: Cell-fusion-mediated somatic-cell reprogramming can be induced in culture; however, whether this process occurs in mammalian tissues remains enigmatic. Here, we show that upon activation of Wnt/β-catenin signaling, mouse retinal neurons can be transiently reprogrammed in vivo back to a precursor stage. This occurs after their spontaneous fusion with transplanted hematopoietic stem and progenitor cells (HSPCs). Moreover, we demonstrate that retinal damage is essential for cell-hybrid formation in vivo. Newly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 58 publications
1
101
1
Order By: Relevance
“…3a). In contrast to corneal studies, the role of WNT signaling in the posterior pole has been examined in various parts of the tissue, such as the neural retina, retinal vasculature and retinal pigment epithelium [24][25][26][27][28] . To evaluate the expression pattern of WNT7B in the posterior pole of eyes, we examined the localization of WNT7B in the mouse eye.…”
Section: Resultsmentioning
confidence: 99%
“…3a). In contrast to corneal studies, the role of WNT signaling in the posterior pole has been examined in various parts of the tissue, such as the neural retina, retinal vasculature and retinal pigment epithelium [24][25][26][27][28] . To evaluate the expression pattern of WNT7B in the posterior pole of eyes, we examined the localization of WNT7B in the mouse eye.…”
Section: Resultsmentioning
confidence: 99%
“…They express the same neurogenic genes, such as Notch and Wnt, as those found in the fish 17,18 , and can be reprogrammed in a dish to become retinal neural or photoreceptor progenitors 19,20 . In vivo, it has been shown that, by targeting specific signaling pathways through administering fibroblast growth factor (FGF) 21 , Notch 22,23 , Wnt [24][25][26] , or sonic hedgehog 27 , a significant number of Müller cells can be induced to re-enter the cell cycle and display properties of retinal progenitors. While transcription factor Ascl1a was shown to be required for retinal regeneration in the fish 12,14,28 , recent report indicates that overexpressing a single transcription factor, Ascl1, is also sufficient to induce a neurogenic state of mature Müller cells of mice 29 .…”
Section: Sources Of Endogenous Stem Cells/progenitor Cellsmentioning
confidence: 99%
“…Thus far, approaches have been based on surgical reconnection of transected mammalian nerve fibres, combined with the application of polymers such as polyethylene glycol (PEG) [72][73][74][75][76][77] . The mechanism through which PEG acts is not clear, but it is proposed to work like a fusogen by facilitating membrane merging 72 . It has had very promising results in vivo, with evidence of both morphological and functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were predominantly performed in rat sciatic nerves, but also more recently have included a small clinical trial directed at repairing damaged human digital nerves 78 . Development of these techniques has been directly attributed to observations of endogenous fusion mechanisms in invertebrates 72 . One could speculate that EFF-1 or AFF-1 would also be promising candidates for inducing fusion at these injury sites, provided we gain a better understanding of their fusogenic activity and regulation in neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation